55 (3eTcdI MHs - (3eMehO, eUWajs 1921 - 2009 ((3GdbGgQIs (3ecJHI eUQs, 2013)
(3GdcJGH YHGQI Yf QSGFd eNJGQI ef GYJQGaGJ heTcdGJ bQGA (B"(3GdOcJhQ eUWai eMehO(B" (3efgG GdeVMc hefgG GdeHcj(B.. (3fSeY GdcKjQ jbhdhf (B"(3GdMH aj GdRef GdLejd(B" (3Cj aj aJQI GdNeSjfjGJ h GdSJjfjGJ, hgj GdaJQI GdJj ocJH ajgG GdcJGH(B.. (3EdG CffG dG fdeS LeGd Pdc GdMH ceG UqhQhg(B.. (3abO WZi Ydi Pdc GdYUQ UQGY GdWHbGJ, hJMce GdeGd HGdEfSGf, hGfYOGe GdKbI, hGdJMdd hGdGfaJGM, hJOfj GdCNdGb, cdgG JLeYJ dfSL CcGPjH Mhd GdMH(B.. (3MjK cGf eaghe GdMH eThTkG dOi GdcKjQjf aj Pdc GdReGf, NGdjkG ef Gdbje GdEfSGfjI hGdefWbjIs
1 12 14
Keywords: (3GdCOH GdYQHjs; (3GdebGdGJ GdYQHjIs -- (3eUQs